Waste minimization and cost reduction for the process industries - Cheremisinoff, Paul N. (Noyes Publications, 1995)
The purpose of this book is to provide a base of information and analysis to assist in implementation of the policy of reducing and/or minimizing hazardous waste generation in manufacturing and more specifically in the process industries. What is the significance of reducing the generation of all process wastes? This book examines the technical nature of waste reduction and the extent to which waste reduction can likely be implemented. Also explored is the extent to which technology itself, as well as information and resources, is a barrier to waste reduction. In what ways are waste reduction.